Influence of Ti–O–Si hetero-linkages in the photocatalytic degradation of Rhodamine B - Rasalingam, Shivatharsiny; Kibombo, Harrison S.; Wu, Chia-Ming; Baltrusaitis, Jonas; Koodali, Ranjit T. (Catalysis communications, 2013)
The influence of Ti–O–Si hetero-linkages in the degradation of Rhodamine B (RhB) dye over TiO2–SiO2 xerogels is exemplified by XPS analysis. We demonstrate a relationship between the percentage surface content of Ti–O–Si and the rate of photocatalytic degradation of RhB. Our detailed surface investigation revealed that the overall degradation of RhB is enhanced due to the high surface percentage content of Ti–O–Si species, high crystallinity of titania phase, and its effective dispersion on a high surface area porous silica support.
Keywords: Titania; Mixed oxide; Surface characterization; Photocatalysis